2013
DOI: 10.1158/1078-0432.ccr-12-3606
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling Defines Subtypes of Prostate Cancer with the Potential for Therapeutic Stratification

Abstract: The remarkable variation in prostate cancer clinical behavior represents an opportunity to identify and understand molecular features that can be used to stratify patients into clinical subgroups for more precise outcome prediction and treatment selection. Significant progress has been made in recent years in establishing the composition of genomic and epigenetic alterations in localized and advanced prostate cancers using array-based technologies and next generation sequencing approaches. The results of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 69 publications
(102 reference statements)
1
54
0
Order By: Relevance
“…Due to the breadth of the topic and recent high-quality reviews, we have specifically focused on genomic tests that are already available or approaching the point of clinical use [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the breadth of the topic and recent high-quality reviews, we have specifically focused on genomic tests that are already available or approaching the point of clinical use [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…3 Hypermethylation of promoter CpG islands (CGIs) can silence tumor suppressor genes early during tumorigenesis, while significant global hypomethylation arises later in PCa progression. [4][5][6] It is likely that different patterns of DNA methylation may distinguish aggressive vs. indolent PCa and predict responses to specific treatments. Earlier studies have shown that promoter hypermethylation of specific genes are associated with PCa progression.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that tumor-associated genomic aberrations may be utilized for cancer screening, diagnosis, risk prognosis, therapy prediction and outcome assessment (30)(31)(32). Blood PSA tests are frequently used to screen and detect early-stage cancer (33).…”
Section: Genetic Biomarkers For Screening and Detection Of Early Cancermentioning
confidence: 99%
“…Individual patients have a distinct pattern of genetic alterations; therefore, treatment should be guided by the profile of diagnostic biomarkers (14,22,32). The AR signaling axis is a major target for numerous hormone therapies, throughout the stages of cancer (59)(60)(61).…”
Section: Therapies Targeting To Tumor Genetic Aberrationsmentioning
confidence: 99%